2017
DOI: 10.1590/s1517-707620170001.0130
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento reológico do Bio-PE e do PCL na presença do PEgAA e PEgMA

Abstract: RESUMOO reômetro de torque é um equipamento que reproduz em escala laboratorial o processamento de polímeros. Neste equipamento, a velocidade de rotação dos rotores, temperatura e tempo de processamento são parâme-tros predeterminados e impostos ao sistema investigado; avalia-se o torque necessário para a fusão, mistura e homogeneização da amostra. Através do gráfico do torque em função do tempo e do gráfico da temperatura em função do tempo de processamento, cujos valores estão relacionados com as propriedade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
4
6
0
2
Order By: Relevance
“…Addition of PEgAA increased the interfacial adhesion, due to the chemical interaction between the hydroxyl group of PCL and the acrylic acid group, as also reported by Bezerra et al (2017a). Therefore, the incorporation of PEgAA provided a better ad-hesion among the phases, decreasing the dispersed phase and contributing to the morphology stabilization of polymer blends compared to the noncompatibilized ones (Sánchez et al, 2001, Moura et al, 2008, Liu et al, 2011, Pracella, 2016Agrawal et al, 2018).…”
Section: Sem Images Of Binary Blends' Dispersed Phase Extraction Is Pmentioning
confidence: 59%
See 1 more Smart Citation
“…Addition of PEgAA increased the interfacial adhesion, due to the chemical interaction between the hydroxyl group of PCL and the acrylic acid group, as also reported by Bezerra et al (2017a). Therefore, the incorporation of PEgAA provided a better ad-hesion among the phases, decreasing the dispersed phase and contributing to the morphology stabilization of polymer blends compared to the noncompatibilized ones (Sánchez et al, 2001, Moura et al, 2008, Liu et al, 2011, Pracella, 2016Agrawal et al, 2018).…”
Section: Sem Images Of Binary Blends' Dispersed Phase Extraction Is Pmentioning
confidence: 59%
“…This increase was approximately 83.5% for Bio-PE/PCL/ PEgAA (80/20/10 w/w/phr) and 60.5% for Bio-PE/PCL/PEgAA (70/30/10 w/w/ phr). This behavior can be associated to the higher adhesion among the phases increasing PCL content (20 and 30%), as a result of reaction between acrylic acid groups and hydroxyl ones of PCL, as well as the miscibility of PEgAA with Bio-PE, which properly promotes stress transferring from one to each other phase (Deblieck et al, 2011;Silva, 2014;Bezerra et al, 2017a;Chudnovsky and Sehanobish, 2017;Agrawal et al, 2018). Even though addition of the coupling agent did not improve the impact strength, when compared to a respective blend without functionalized copolymer, the morphology reached by SEM showed that the dispersed phase decreased and the morphology stabilized.…”
Section: Impact Strength Measurementsmentioning
confidence: 99%
“…DSC scans acquired during the second heating are presented in Figure 2 The Molten Fraction plots presented a sigmoidal shape characteristic of phase transformation in polymers without discontinuities, behavior similar to that observed during crystallization from the melt (Relative Crystallinity); these curves are presented in Appendix 3, Figures A8-A11. The melting rates of PCL and Bio-PE increased in the blends with values between 30-50% higher than in the neat resins, which can be understood as a facilitated melting process, thus providing a processing with less energy consuming and possibly cheaper [23,24] .…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 92%
“…These results are linked to the morphological effect among the phases, despite the immiscible character (as observed by DSC scans Figure 2, SEM images Figure 3, Table A1-A4 and Figures A6-A7 of Appendix 2 and 3), in the amorphous phases of both polymers, secondary interactions are possible to occur, additionally PEgMA contributes to better mechanical performance. SEM images captured with the aim of a better enlightenment, and shown further on [30,33,34] , suggest the Elongation at Break of Bio-PE/PCL blends, being the ternary systems with addition of the functionalized copolymer PEgMA improved (higher), which can be resulted from the reaction between maleic anhydride with the hydroxyl (OH) end groups of PCL that may be taken place providing an interface with higher performance, behaviors which can be inferred from decreases in dispersed phase as showed in Figure 3 and Table 4 by dispersed phase's average diameter measurements [24,25,[35][36][37][38][39][40] .…”
Section: Mechanical Tests -Tensile Strengthmentioning
confidence: 94%
See 1 more Smart Citation